LIVING HADIS PADA PROSESI KHATAMAN ALQURAN DI PONDOK PESANTREN SUNAN PANDANARAN YOGYAKARTA: STUDI KONTEKSTUALISASI PENDIDIKAN DENGAN TAKHRÃ®J AL-á¸¤ADÃ®TH - Hakiemah, Ainun; Sakhok, Jazilus; Munandar, Siswoyo Aris (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2020)
The tradition of khataman al-Qur?an routinely in Tahfidz Boarding School at Krapyak Yogyakarta, Sunan Pandanaran Yogyakarta Boarding School (pesantren), Al-Asy'ariyah Wonosobo Boarding School (pesantren), Al-Muayyad Solo Boarding School (pesantren), and so on. The term "khataman" in such pesantren is a term aimed at the annual activities of the completion of some students in memorizing juz ?amma, certain letters from the Alquran determined by the pesantren, and especially because of the students who have completed memorizing al- Qur'an 30 juz. The traditions and phenomena of khataman and graduation, especially at the Sunan Pandanaran Islamic Boarding School, need to be reviewed as to how they are from the perspective of the Prophet's tradition. Therefore, in this paper we will explore  about the Prophet's traditions (takhrij al-hadith) related to the "Khataman al-Qur'an" and also try to do study the sanad and matan hadith. The hadith search used to stand is the e-hadith application and Gawame Alkalim application.